A STUDY OF CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND HARDINESS IN YOUNG WIVES - Karunia Dewi Nainggolan; Arthur Huwae (Kafa`ah: Journal of Gender Studies, 2022)
In many parts of the world, early marriage is a persisting problem. The number of early marriage in Indonesia increases every year and, if the condition persists, will pose a serious risk for the young brides both physically and mentally. Psychologically, young brides experience burdens and pressures from internal and external sources hence they need tough personality (hardiness) along with the awareness of developing emotional intelligence to overcome this stressful situation. This study aims to determine the relationship between emotional intelligence and hardiness in young brides, with the use of correlational quantitative method. The study involves 34 young brides as subjects, gathered through purposive sampling technique. The research makes use of two scales, namely emotional intelligence scale and hardiness scale. The test results show that there is a significant positive relationship between emotional intelligence and hardiness. This indicates that well-formed emotional intelligence enables young brides to toughly and strongly cope with their marriage life.